Program Pengembangan Kompetensi Teknologi Informasi Di Sman 1 Talang Ubi (Pali): Workshop Dan Pelatihan Untuk Meningkatkan Keterampilan Digital Siswa - Antoni, Darius; Kartina, Riza; Fadillah, Arif; Hermizahadiwidastra, Hermizahadiwidastra (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The development of information and communication technology (ICT) requires students to have adequate digital skills as provisions in facing the challenges of modern education and the world of work. However, the digital divide is still a serious problem in various non-metropolitan areas, including in Penukal Abab Lematang Ilir (PALI) Regency, South Sumatra. This community service program aims to improve digital literacy and competence of SMAN 1 Talang Ubi students through intensive training and workshops. The implementation method includes initial needs assessment, preparation of training modules, implementation of practice-based workshops, and evaluation of student competency achievement. Training materials include the use of productivity software, basic data processing, introduction to programming, and digital ethics. The results of the activities showed a significant increase in students' understanding and skills in the field of ICT, as well as the emergence of interest in further exploration in the field of technology. This program not only has a positive impact on students' mastery of digital skills, but also contributes to building a sustainable digital learning ecosystem in the school environment.